The rhetoric of aesthetics: the beauty of the traditional Roman rite of the Mass - Wachs, Anthony M. (Kansas State University, 2008)
This thesis is a response to a contemporary debate over the nature of rhetoric. Specifically, it has recently been declared that rhetoric is aesthetic. This move is known as the "aesthetic turn" and it has been both praised and denounced by rhetoric scholars. An aesthetic rhetoric is concerned not with the content of a message, but rather with the presentation of the message. In this thesis, I argue that an aesthetic turn is a good turn to make in theory, but that the actual turn taken by a number of prominent rhetorical scholars has been misguided. A Catholic theory of beauty is developed within this thesis as an alternative to the postmodern aesthetic. The Catholic theory posits that beauty flows from three forms: the accidental, the substantial, and the transcendental. Accidental beauty is concerned with physical traits and can be judged through integrity, proportion, and splendor. Substantial beauty deals with an object's telos or end and is judged according to the actualization of telos. Transcendental beauty is a trait of all beings and can be judged hierarchically according to participation in Being. Finally, a methodology for analyzing beauty is developed within the thesis. In order to reify the Catholic theory of beauty and its methodology the Roman Catholic Mass of 1962, also known as the Tridentine Mass, is analyzed as a case study. This artifact was chosen in particular because it was recently liberated from bureaucratic imprisonment by Pope Benedict XVI. In addition to analyzing the traditional Roman rite, several changes that were made to the Mass after the Second Vatican Council are examined. This study is important for several reasons. First, it provides rhetorical scholars with a clear understanding of beauty with which rhetoric can be analyzed. Also, the aesthetic theory offered by this study transcends the differences between rhetoric-as-epistemic and rhetoric-as-aesthetic scholarship. Most importantly though, view of beauty that is advanced implies an ethic from which rhetoric can be evaluated. Finally, the study has important implications for the development of the Roman Catholic liturgy.
Keywords: Rhetoric and Aesthetics; Aesthetic Turn; Beauty; Ethics; Roman Catholicism; Roman Catholic Mass; Language, Rhetoric and Composition (0681); Religion, General (0318); Speech Communication (0459)